Optimalisasi Urban Farming menggunakan System Monitoring Soil Moisture - Ahmad Taqwa; Lindawati Lindawati; Abdurrachman Faiz (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
Lack of green land in urban areas makes gardening difficult. The high mobility of city residents makes gardening on urban agricultural crops. However, these problems can be overcome by gardening with a controlled urban farming system. In this research a monitoring system is designed that can read soil moisture in the urban farming system. The humidity monitoring system is carried out by implementing the YL-69 sensor which will determine the level of soil moisture. This Soil Moisture Monitoring System will be connected to the Internet of Things (IoT) which will display data in real time. The output of the YL-69 type humidity sensor in real time is required using the Web-based IoT Platform, Thingspeak. With this system, it is expected that the community can be more efficient and productive in conducting gardening activities in urban areas